Radiation dosage during pediatric diagnostic or interventional cardiac catheterizations using the "air gap technique" and an aggressive "as low as reasonably achievable" radiation reduction protocol in patients weighing < 20 kg - Frank A Osei; Joshua Hayman; Nicole J Sutton; Robert H Pass (Wolters Kluwer Medknow Publications, 2016)
Background: Cardiac catheterizations expose both the patient and staff to the risks of ionizing radiation. Studies using the "air gap" technique (AGT) in various radiological procedures indicate that its use leads to reduction in radiation exposure but there are no data on its use for pediatric cardiac catheterization. The aim of this study was to retrospectively review the radiation exposure data for children weighing <20 kg during cardiac catheterizations using AGT and an "as low as reasonably achievable (ALARA)" radiation reduction protocol. Patients and Methods: All patients weighing <20 kg who underwent cardiac catheterization at the Children's Hospital at Montefiore (CHAM), New York, the United States from 05/2011 to 10/2013 were included. Transplant patients who underwent routine endomyocardial biopsy and those who had surgical procedures at the time of the catheterizations were excluded. The ALARA protocol was used in concert with AGT with the flat panel detector positioned 110 cm from the patient. Demographics, procedural data, and patient radiation exposure levels were collected and analyzed. Results: One-hundred and twenty-seven patients underwent 151 procedures within the study period. The median age was 1.2 years (range: 1 day to 7.9 years) and median weight was 8.8 kg (range: 1.9-19.7). Eighty-nine (59%) of the procedures were interventional. The median total fluoro time was 13 min [interquartile range (IQR) 7.3-21.8]. The median total air Kerma (K) product was 55.6 mGy (IQR 17.6-94.2) and dose area product (DAP) was 189 Gym2 (IQR 62.6-425.5). Conclusion: Use of a novel ALARA and AGT protocol for cardiac catheterizations in children markedly reduced radiation exposure to levels far below recently reported values.